2020
DOI: 10.3389/fvets.2020.588051
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Glucosinolates Might Result in Low Methane Emissions From Ruminants Fed Brassica Forages

Abstract: Methane is formed from the microbial degradation of feeds in the digestive tract in ruminants. Methane emissions from ruminants not only result in a loss of feed energy but also contribute to global warming. Previous studies showed that brassica forages, such as forage rape, lead to less methane emitted per unit of dry matter intake than grass-based forages. Differences in rumen pH are proposed to partly explain these low emissions. Rumen microbial community differences are also observed, but the causes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
5
0
1
Order By: Relevance
“…Therefore, the full mechanisms for the CH 4 mitigation properties of forage brassicas remain unclear to date. Sun (48) proposed a new hypothesis based on a literature review to explain the low enteric CH 4 emission observed from ruminants fed forage brassica. According to the hypothesis, glucosinolates, a secondary metabolite widely present in forage brassica or their breakdown products, can stimulate the secretion of free triiodothyronine in ruminants.…”
Section: Fresh Forage Carbohydrate Composition and Ch 4 Emissions Fro...mentioning
confidence: 99%
“…Therefore, the full mechanisms for the CH 4 mitigation properties of forage brassicas remain unclear to date. Sun (48) proposed a new hypothesis based on a literature review to explain the low enteric CH 4 emission observed from ruminants fed forage brassica. According to the hypothesis, glucosinolates, a secondary metabolite widely present in forage brassica or their breakdown products, can stimulate the secretion of free triiodothyronine in ruminants.…”
Section: Fresh Forage Carbohydrate Composition and Ch 4 Emissions Fro...mentioning
confidence: 99%
“…Brassica forages have also been shown to result in lower CH 4 yields in lambs than perennial ryegrass [ 66 ]. The reason for this is not understood but an altered rumen microbiota or the presence of bioactive glucosinolates in brassicas have been suggested as possible causes [ 67 ]. Generally, however, it takes large changes in diet to bring about significant changes in enteric methane emissions in ruminants.…”
Section: Redirecting Hydrogen Metabolism and Ruminant Methane Mitigationmentioning
confidence: 99%
“…Systemic effects are manifested by iodine deficiency, hypertrophy of kidney, liver and the thyroid gland followed by an elevated secretion of thyroid hormones (Tripathi & Mishra, 2007), which is associated with an increased digesta efflux and consequently reduced rumen retention time (Barnett et al ., 2012). Despite the overly negative effects on animal physiology, the use of glucosinolates‐containing fodder can improve environmental health by mitigating methane emissions by ruminants (Dillard et al ., 2018; Sun, 2020). Mechanistically, glucosinolates do not directly inhibit the methanogenic microbes, but are supposed to alter the microbial community and rumen fermentation parameters (Kumar et al ., 2018; Sun, 2020).…”
Section: Glucosinolates In Soil Animal and Human Healthmentioning
confidence: 99%
“…Despite the overly negative effects on animal physiology, the use of glucosinolates‐containing fodder can improve environmental health by mitigating methane emissions by ruminants (Dillard et al ., 2018; Sun, 2020). Mechanistically, glucosinolates do not directly inhibit the methanogenic microbes, but are supposed to alter the microbial community and rumen fermentation parameters (Kumar et al ., 2018; Sun, 2020). Hence, together with the aforementioned indirect effect of reduced rumen retention time, methane production decreases and interestingly, seems to persist when dairy cows continue to feed on pastures (Storlien et al ., 2017).…”
Section: Glucosinolates In Soil Animal and Human Healthmentioning
confidence: 99%